Sepsis prevalence among patients with suspected infection in emergency department: a multicenter prospective cohort study. (October 2020) - Oberlin, Mathieu; Balen, Frederic; Bertrand, Lionel; Chapeau, Noellie; San Cirilo, Bastien; Ruols, Emmanuelle; Vandercamere, Thomas; Souchaud, Clement; Guedj, Jean François; Konan, Bertille; Duval, Alice; Mur, Sebastien; et al.
Abstract : Objective: In the emergency department (ED), the early identification of patients suspected of infection is a challenge for emergency physicians. Sepsis prevalence among patients with suspected infection in the ED remains uncertain. Our objective was to determine how many cases of sepsis occurred among patients with suspected infections in the ED. Methods: This multi-center, prospective, observational study was conducted in 19 EDs in France. For 1 week, all consecutive ED patients with suspected infection (according to the emergency physician) were included. The primary endpoint was the prevalence of sepsis in the ED according to the 'sepsis-3' definition. Secondary endpoints involved comparisons among patients with and without sepsis. Results: During the study period, 13 904 patients were screened; 494 (3.6%) consulted for suspected infection and were included in the study. Among them, 172 patients [39%, 95% confidence interval (CI) (34–44)] were diagnosed with sepsis. The total hospital mortality for patients with a suspected infection was 4.7% and the hospital mortality for sepsis patients was 9.9%. Conclusion: In the ED, among patients with a suspected infection, the prevalence of sepsis as per the 'sepsis-3' definition was 39% [95% CI (34–44)].